NARRA - Open and Non-linear Narrative - Rosenzveig, Eric (Iluminace, 2015)
Introduction to the content of the software project NARRA, which is in its third year of implementation at the Centre for Audiovisual Studies of the Film and Television Faculty of AMU. It is a multi-purpose and modular environment allowing individual participants to collaboratively create branched and annotated media works using video, sound, images and texts.
Keywords: computers and film; video art; video and film; digital media and film; electronic media and film; audiovisual resources